Longitudinal analysis of hsa-miR-3163, hsa-miR-124-3p, hsa-miR-548c-3p, and hsa-miR-27a-3p as prognostic biomarkers in HIV-infected patients - Balkan, Ilker Inanç; Shahzadi, Andleeb; Sönmez, Haktan; Oktan, Burhaneddin; Umar, Muhammad Ihtisham; Mete, Bilgül; Tabak, Fehmi; Deniz, Günnur; Küçüksezer, Umut Can (Frontiers in Immunology, 2025)
IntroductionMicroRNAs (miRNAs), key regulators of cellular pathways, play crucial roles in the pathogenesis of various diseases, including Human Immunodeficiency Virus (HIV). This study aimed to evaluate the expression and diagnostic potential of in silico-identified miRNAs (miR-124-3p, miR-27a-3p, miR-548ac-3p, miR-3163) before and during antiretroviral treatment (ART), together with their correlations with immunological markers (CD4 count, CD4/CD45 ratio) and virological parameters (HIV RNA load).MethodsBlood samples and clinical data of 16 patients were collected at 4 different time points; before the initiation of ART (baseline), 1st, 2nd and 6th months following HIV diagnosis. 16 healthy controls were enrolled to this study. RT-qPCR and ELISA techniques were used to analyze miRNA expression levels while immunological markers (CD4 count and ratio) were assessed by flow cytometry.ResultsmiR-27a-3p expression was significantly increased at 2nd and 6th months of ART (p<0.001). miR-548ac-3p was upregulated at 6th month compared to healthy individuals and ART-naive subjects (p<0.05). miR-124-3p expression was significantly elevated in ART-naive subjects in comparison with healthy controls (p<0.001). Conversely, miR-3163 was downregulated in ART-naive, 1-month, and 2-month ART groups (p<0.001), but returned to normal levels by 6 months. miR-548ac-3p and miR-3163 showed moderate-to-strong positive correlations with CD4 counts (R=0.46, R=0.67; p<0.001). ROC analysis identified miR-3163 as a promising prognostic marker, with an AUC of 0.8561, (95% CI: 0.756–0.9265).DiscussionOur findings highlight the potential of miR-3163 as a robust prognostic biomarker for monitoring HIV progression and optimizing ART strategies. Validation in larger cohorts is warranted to confirm its clinical utility.